Competency-based learning guide in beverage management - Guggenheim, Liza Jacob; Tumanan, Mary Ann Ramos (Manila, Philippines: C & E Publishing, 2007)
This book focuses on the basics of alcoholic and non-alcoholic beverage products particularly wines, spirits, beers, coffee, tea and soft drinks. It provides fundamental knowledge, learning information, and other key elements that are equally important and structured in a manner to ensure clarity and consistency in the conduct of each module in order to achieved the desired learning results.
Module 1. the senses and wine evaluation -- Module 2. Table wines- red, white and rose -- Module 3. Sparkling wines and champagne -- Module 4. Fortified wines- sherry, port and mandeira -- Module 5. Aromatized wines, vermouth, bitter and anise -- Module 6. Philippine distilled spirit and wines- basi, tapuy, tuba and lambanog -- Module 7. Brown distilled spirits -- brandy, whisky and rum -- Module 8. White distilled spirit- gin, vodka and tequilla -- Module 9. Liquers -- Module 10. Beers and ales -- Module 11 A. Non-alcoholic beverages - coffee -- Module 11 B. Non-alcoholic beverages - tea -- Module 11 C. Non-alcoholic beverages - softdrinks .
Keywords: BEVERAGES MANAGEMENT; GUIDEBOOK